2020
DOI: 10.3390/microorganisms8071060
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Response of Wolbachia pipientis in a Cell-Free Medium

Abstract: Wolbachia, an obligate intracellular bacterium estimated to infect millions of arthropod species worldwide, is currently being utilized in novel control strategies to limit the transmission of Dengue and Zika viruses. A limitation for Wolbachia-based control approaches is the difficulty of transferring Wolbachia to novel hosts and the lack of tools for the genetic transformation of Wolbachia due to the inability to culture Wolbachia outside the insect host cell in an axenic media. Here, we applied extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The possibility therefore exists of transfecting mosquitoes with specific strains of Serratia to control malaria although much additional work is required and Wolbachia -based strategies have been given priority at the present time [ 62 64 ]. However, as mentioned earlier in this article, the use of Wolbachia in paratransgenesis has not been developed so far as the bacterium cannot be genetically transformed and is difficult to culture (it is an obligate intracellular symbiont) [ 56 , 57 , 212 ]. Reveillaud et al [ 213 ], however, reported Wolbachia from four wild Culex pipiens mosquitoes carrying a plasmid (pWCP), indicating that future paratransgenesis utilising Wolbachia may be possible.…”
Section: Paratransgenesis In Different Groups Of Vectorsmentioning
confidence: 99%
“…The possibility therefore exists of transfecting mosquitoes with specific strains of Serratia to control malaria although much additional work is required and Wolbachia -based strategies have been given priority at the present time [ 62 64 ]. However, as mentioned earlier in this article, the use of Wolbachia in paratransgenesis has not been developed so far as the bacterium cannot be genetically transformed and is difficult to culture (it is an obligate intracellular symbiont) [ 56 , 57 , 212 ]. Reveillaud et al [ 213 ], however, reported Wolbachia from four wild Culex pipiens mosquitoes carrying a plasmid (pWCP), indicating that future paratransgenesis utilising Wolbachia may be possible.…”
Section: Paratransgenesis In Different Groups Of Vectorsmentioning
confidence: 99%
“…While some success has been reported using random mutagenesis to introduce genetic variation in the Wolbachia genome (Duarte et al, 2020), mutant identification and linkage with a Wolbachia-conferred phenotype remains a challenge. Wolbachia do not replicate outside of their host cells and not yet genetically editable (Rasgon et al, 2006), thus efforts are impending to investigate cellular factors required for Wolbachia growth and replication in the host cell-free system (Krafsur et al, 2020). The main challenges to achieve Wolbachia transformation involve (i) genetic constructs crossing the eukaryotic membrane, (ii) protecting DNA from cellular nucleases and degradation inside the eukaryotic cell, (iii) crossing the bacterial membrane, and (iv) stable and selectable incorporation into the Wolbachia genome.…”
Section: Genetic Manipulation Of Wolbachiamentioning
confidence: 99%
“…It can manipulate the reproduction of its hosts, inducing reproductive alterations, such as cytoplasmic incompatibility, feminization, male death and parthenogenesis to increase its transmission and persistence in the environment (Rocha et al, 2018;Bagheri et al, 2019;Mateos et al, 2020). Maternal transmission, Wolbachia's reproductive advantage, can block the transmission of pathogens (Krafsur et al, 2020) and influence insect fitness (Cao et al, 2019), important variables in the rearing of natural enemies.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%